Low-dose aspirin and heparin treatment improves pregnancy outcome in recurrent pregnancy loss women with anti-β2-glycoprotein I/HLA-DR autoantibodies: a prospective, multicenter, observational study - Tanimura, Kenji; Saito, Shigeru; Tsuda, Sayaka; Ono, Yosuke; Deguchi, Masashi; Nagamatsu, Takeshi; Fujii, Tomoyuki; Nakatsuka, Mikiya; Kobashi, Gen; Arase, Hisashi; Yamada, Hideto (Frontiers in Immunology, 2024)
Introduction Anti-β2-glycoprotein I (β2GPI)/human leukocyte antigen (HLA)-DR antibodies may be a risk factor for recurrent pregnancy loss (RPL). The therapeutic modality for women with RPL and anti-β2GPI/HLA-DR antibody positivity has not been evaluated. This prospective, multicenter, observational study aimed to assess whether low-dose aspirin (LDA) and/or heparin therapies improve pregnancy outcomes in women with RPL who tested positive for anti-β2GPI/HLA-DR antibodies. Methods Between August 2019 and December 2021, 462 women with RPL underwent anti-β2GPI/HLA-DR antibody measurements and risk assessments for RPL. Each attending physician decided the treatment modality for women with RPL who tested positive for anti-β2GPI/HLA-DR antibodies, and their pregnancy outcomes were followed up until December 2023. Finally, 47 pregnancies in 47 women with RPL and anti-β2GPI/HLA-DR antibody positivity were included in the analysis and were divided into two groups regarding whether they were treated with LDA and/or unfractionated heparin (UFH) (LDA/UFH group, n = 39) or with neither of them (non-LDA/non-UFH group, n = 8). The rates of live birth and pregnancy complications (i.e., preeclampsia and preterm delivery before 34 gestational weeks due to placental insufficiency) were compared between the two groups. Results The live birth rate in the LDA/UFH group was higher than that in the non-LDA/non-UFH group (87.2% vs 50.0%, p = 0.03). The pregnancy complication rate in the LDA/UFH group was significantly lower than that in the non-LDA/non-UFH group (5.9% vs 50.0%, p = 0.048). Among 21 women who tested positive for anti-β2GPI/HLA-DR antibodies and had no other risk factors for RPL, the live birth rate in the LDA/UFH group (n = 14) was much higher than that in the non-LDA/non-UFH group (n = 7) (92.9% vs 42.9%, p = 0.03). Discussion This study, for the first time, demonstrated that LDA and/or UFH therapies are effective in improving pregnancy outcomes in women with RPL and aβ2GPI/HLA-DR antibody positivity.